Fish welfare in a changing world: New developments and current challenges - Sonia Rey Planellas; João L. Saraiva; Eliane Gonçalves‐de‐Freitas; Pablo Arechavala‐Lopez; Bernice Bovenkerk; Michael Breen; Steven J. Cooke; Martin Føre; Lene Northwood; Lars Helge Stien; Sunil Kadri; Chris Noble; et al. (Journal of Fish Biology, 2026)
The welfare of non‐human animals is central to ethical discussions on animal use, with increasing attention to fish welfare across research, aquaria, aquaculture, and fisheries. This paper reviews current theoretical approaches to animal welfare and recent advances in defining and assessing fish welfare since the seminal paper by Huntingford et al. (2006; J Fish Biol 68 : 332–372), highlighting the growing role of cognitive and affective processes. It also includes the concept of positive welfare and some of the current research advances in this field. Methods for measuring, monitoring and assessing welfare via the utilisation of outcome‐ and input‐based indicators are outlined, ranging from practical operational tools to laboratory‐based measures. Welfare concerns in wild‐capture fisheries are examined in relation to stress, flesh quality and sustainability, including the welfare of released fish. Recent advances in fish neurobiology, cognition and pain perception are summarised, together with technological innovations that enhance welfare monitoring and management. The paper also explores the relationship between fish welfare, sustainability, public concerns and consumer demand, and legal and moral recognition across contexts, situating fish welfare within the ‘One Health’ and ‘One Welfare’ frameworks that link animal welfare, environmental stewardship and human well‐being. Ongoing challenges include climate change, cultural factors and the interpretation of fish sentience and cognition among others.